Verbal Memory in Late-life Depressions and Normal Ageing - Balashova, E; Zarudnaya, E (KnE Life Sciences, 2018)
In the present article, authors analyze characteristics of verbal memory in late-life depressions and normal ageing. During last decades, the increase of frequency of affective disorders in depression spectrum in late age attracts attention of specialists. Memory is one of the most sensitive functions in late-life depressions. The main goal of this research is to estimate verbal memory of senior patients with depression and normal persons. Two groups of participants, consisting of 197 patients with depressions of Scientific Center of Mental Health (Moscow) and 100 mentally healthy people participated in this research. Control and clinical groups were comparable by socio-demographical parameters. The results of two methods were interpreted: (1) memorization and delayed reproduction of five words; (2) naming of five sharp objects. In first method, the volume of first reproduction (FR), the number of material presentations required for memorization (N) and the volume of delayed reproduction (DR) were examined. In addition, the frequency of occurrence of various types of errors such as omissions, inert repetitions, impairments of order and of selectivity was estimated. In the second method were examined: presence of pauses, necessity of psychological assistance, such as verbal stimulation or clarification of the semantic field. Statistical analysis was made using SPSS Statistics and Microsoft office Excel 2007. The research results showed that patients with depression deal with offered methods worse than mentally healthy people do. In memorization of five words, volumes of FR and DR were lower and patients needed more repetitions to memorize. When analyzing age dynamic, negative changes in verbal memory were more evident in clinical group. When naming of five sharp objects, patients with depression made more pauses and needed more frequently clarification of semantic field or verbal stimulation. Keywords: verbal memory, normal ageing, late-life depressions, neuropsychology